The Bulgarian Entrepreneurship During the Crisis and as an Engine of the Post-Crisis Development (UNWE Yearbook, 2014)
The study analyses significant and topical for the current situation problems – how entrepreneurial activity supports the economy to cope with the crisis and how the innovative and strategically oriented entrepreneurs can become an engine of its post-crisis development.There are few available investigations at micro level on the evidences and causes of the current global economic crisis, which examine the concrete behavior of individual entrepreneurs and firms in crisis situations. An international conference on entrepreneurship held in Bulgaria in September 2010 has a definite contribution in this direction. Results of researches from different countries have been presented at the conference and they are used in the study.The economic crisis has a great impact on the Bulgarian entrepreneurs and companies. In 2009 almost all businesses and economic sectors in the country were affected. To cope with the adverse repercussion of the crisis, the Bulgarian entrepreneurs use not only widely known, but also non-traditional approaches (tricks) for solving problems. To guarantee the success of such actions every entrepreneur has to make their own SWOT analysis – not only to help in surviving the crisis, but also to outline the development prospects after it.Besides all difficulties, the crisis creates many opportunities, from which people with entrepreneurial potential can benefit. But the state should be involved in this by creating conditions for increasing the entrepreneurial activity and supporting enterprises, especially those that make higher value added. The purposeful encouragement and support of the present and future entrepreneurs (the young people in particular) are basic tools for the Bulgarian economy revival and for laying the foundations of its post-crisis development. In this context there is a need for research intensification, the results of which will help the process of making adequate and working decisions for the practice.